The current state and potential evolution of carbon emissions in the healthcare sector: a narrative review article - Mominkhan, Dalia; Alamri, Fahad A.; Balharith, Manea; Alharbi, Muaddi; Alshebli, Ahmed; Alshareef, Sara Y.; Khairaldain, Abdulhemaid; Almutairi, Najla; Abusit, Abdulaziz; Almuzaini, Yasir; Alahmari, Ahmed A.; Alabdulaali, Mohammed K. (Frontiers in Sustainable Energy Policy, 2023)
Over 98% of the world's greenhouse gas emissions in 2014 came from carbon dioxide (CO2), methane, and nitrous oxide. Over one century, CO2 emissions increased from 3.09 to 37.12 billion metric tons. The healthcare sector is one of the major sources of greenhouse gas emissions. The carbon footprint of a country's healthcare system is influenced by its domestic economy, healthcare expenditure, and energy system. The aim of this study is to present a concise of the present status of carbon emissions within the healthcare sectors on a global scale, as well as the forthcoming endeavors to mitigate these emissions. A narrative review of studies on climate change, carbon emissions, and greenhouse gases in the healthcare sector was conducted using Medline PubMed, Web of Science, Scopus and Google Scholar databases from 2005 to April 2023. According to the data, several countries emit more carbon per capita than others. The Conference of the Parties on Climate Change (COP26) recently encompassed extensive efforts culminating in releasing initiatives toward zero-carbon healthcare sectors. Efforts in some medical practices, smart technology to save energy, digital health, artificial intelligence technology, and monitoring have contributed to reducing carbon emissions. In conclusion, the healthcare sector with zero carbon emissions must be sustainable, adaptable, and efficient while delivering safe, high-quality care. Addressing the sector's carbon footprint requires innovative strategies, a multisector approach, health professionals' participation, community engagement, and regular monitoring of emissions and performance indicators to ensure patient service quality and low carbon emissions in the healthcare sector.